The Interplay of Illocutionary Aspects in Johanna Spyri's Heidi: A Pragmatic Inquiry - Silvana M. Hasan (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2024)
Speech act is a part of pragmatics where there are definite objectives beyond the words or phrases when a speaker says something. A speech act is the utterance of an expression that contains a certain meaning and reference. This study aims to determine the aspects of illocutionary speech acts based on Searle's classification, which includes five types of speech acts. The novel analyzed is Heidi by Johanna Spyri, a fictitious and narrative work portraying characters and actions of human beings, gained from real-life experiences. This research uses a descriptive qualitative method, analyzing illocutionary speech acts in the novel Heidi using Searle's theory. A notable research gap exists in the comprehensive analysis of illocutionary speech acts within classic literature, especially in how these acts contribute to narrative and characterization. This study aims to address this gap by examining 24 utterances identified as illocutionary speech acts in Heidi, categorized into 5 assertive, 9 directive, 3 commissive, 4 expressive, and 2 declarative speech acts. The findings highlight the significant role of illocutionary speech acts in driving the narrative and character interactions in Heidi. Understanding these speech acts can provide deeper insights into character development and plot progression. It is recommended that future studies expand this analysis to other classic literary works to further explore the implications of illocutionary acts. This study underscores the importance of speech act theory in literary analysis, offering a framework for interpreting character intentions and actions beyond the literal meaning of their words.